Adsorption of sulfur dioxide (SO2) gas using treated rice husk ash (RHA) adsorbent / Nurul Najwa Abd Malek and Rusdin Laiman - Abd Malek, Nurul Najwa; Laiman, Rusdin (2018)
The aim of this study was to investigate the potential of treated rice husk ash (RHA) as adsorbent to adsorb acidic SO2 gas. The treated RHA was prepared using a water hydration method by mixing the RHA, Calcium oxide (CaO) and Sodium Hydroxide (NaOH). The addition of NaOH is to increase the dissolution of silica from the RHA to form reactive species responsible for higher desulfurization activity. The untreated and treated RHA were subjected to several characterizations and the characteristics of the adsorbents were compared. The functional groups present on the surface of the adsorbent were determined using Fourier Transform Infrared (FTIR). The chemical composition of the untreated and treated RHA was analyzed by using X-ray Fluorescence (XRF). Scanning electron microscope (SEM) analysis showed that the treated RHA has higher porosity compared to untreated RHA. Based on the SO2 adsorption analysis, it was found that the treated RHA has higher adsorption capacity, 62.22 mg/g, compared to untreated RHA, 1.49 mg/g.